Interaction of monetary and fiscal policies in Turkey - Tayyar Büyükbaşaran; Cem Çebi; Erdal Yılmaz (Central Bank Review, 2020)
This paper aims to investigate the interaction between monetary and fiscal policies in Turkey. For this purpose, a Bayesian Structural Vector Autoregression (SVAR) model with sign and zero restrictions is used. We particularly focus on how the fiscal and monetary policy variables respond to various macroeconomic shocks and whether the type of shocks matters. Our results confirm the importance of nature of shocks in terms of interaction between monetary and fiscal policies with the finding that both policy shocks are complementary in response to demand and supply shocks while they are substitute in response to shocks caused by the each other. Our main findings are robust to alternative variable definitions and identifying restrictions.